2017
DOI: 10.1002/chem.201606024
|View full text |Cite
|
Sign up to set email alerts
|

Highly Selective Turn‐On Fluorescent Chemodosimeter for AlIII Detection through AlIII‐Promoted Hydrolysis of C=N Double Bonds in the 8‐Hydroxyquinoline Aldehyde Schiff Base

Abstract: Fluorescent chemodosimeters based on small organic molecules are widely used in the detection of various analytes. However, chemodosimeters for metal ion detection are still limited to a few transition metals, such as Hg , Cu , Fe , Au , etc. In this work, a fluorescent chemodosimeter of 5-chloro-7-phenyliminomethyl-8-hydroxyquinoline (2) for the detection of Al is reported. Chemodosimeter 2 exhibits a turn-on fluorescence response to Al owing to an Al -promoted hydrolysis of carbon-nitrogen double bonds. This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 40 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…It is reported that excess consumption of levofloxacin may trigger severe adverse symptoms, such as anaphylactic shock, laryngeal edema, tendon rupture, peripheral nervous system damage, and so on. Therefore, it is urgent to investigate a reliable method for detecting levofloxacin in the medical and clinical fields. In recent years, fluorescence-sensing methods have attracted widespread attention because of their quick response, high sensitivity, nondestructive emission signals, low cost, and capability of real-time detection. Employing fluorescence analysis for the determination of levofloxacin is a reliable method.…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that excess consumption of levofloxacin may trigger severe adverse symptoms, such as anaphylactic shock, laryngeal edema, tendon rupture, peripheral nervous system damage, and so on. Therefore, it is urgent to investigate a reliable method for detecting levofloxacin in the medical and clinical fields. In recent years, fluorescence-sensing methods have attracted widespread attention because of their quick response, high sensitivity, nondestructive emission signals, low cost, and capability of real-time detection. Employing fluorescence analysis for the determination of levofloxacin is a reliable method.…”
Section: Introductionmentioning
confidence: 99%
“…Schiff‐base fluorescence 15 (Figure 13)at pH 5.0 in aqueous solution indicated two absorption spectra at the wavelengths of 314 and 456 nm [42] . With the incremental increase in the amount of Al 3+ ion, there is a gradual decrease in two absorption bands, accompanied by the appearance of a new absorption signal at 381 nm.…”
Section: Fluorescent Receptors For Positively Charged Ionsmentioning
confidence: 99%
“…According to the literature, the imine group in the Schiff base could be destroyed by hydrolysis reactions in the acidic solvent. 34 The trivalent metal ion solutions were acidic which could generate acids in protic solvents. 35 Figure 5 clearly demonstrated that the intensity of the fluorescence signal of L in the acidic pH range was almost similar to that achieved in presence of the trivalent metal ions in ethanol.…”
Section: The Sensing Mechanismmentioning
confidence: 99%